2019
DOI: 10.4172/neuropsychiatry.1000552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dielectric Monopolar Radiofrequency with Vacuumtherapy in the Treatment of Chronic Constipation in Patients with Intellectual Developmental Disorders

Abstract: AimChronic constipation is a high prevalence complication in patients with intellectual developmental disorders due to medication intake and physical activity reduction. Several manual therapy techniques have achieved good results at its treatment, being these a considerable option as no adverse effects have been shown. Nevertheless, the use of electrotherapy devices has not been studied on chronic constipation treatment. These may be considered as a potential tool which may supplement treatment. Thermotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A quasi-experimental pre/post study in a population with an intellectual disability indicated the possible use of this technique assisted with vacuum therapy to treat chronic constipation, reporting an increase in the number of stools and a reduction in irritability episodes in an evaluation period of 14 days. In improving the stool quality assessed with the Bristol scale [ 34 ], the physiological changes at the visceral level suggested by this study represent an opening to a wide field of research regarding possible CRET applications.…”
Section: Discussionmentioning
confidence: 99%
“…A quasi-experimental pre/post study in a population with an intellectual disability indicated the possible use of this technique assisted with vacuum therapy to treat chronic constipation, reporting an increase in the number of stools and a reduction in irritability episodes in an evaluation period of 14 days. In improving the stool quality assessed with the Bristol scale [ 34 ], the physiological changes at the visceral level suggested by this study represent an opening to a wide field of research regarding possible CRET applications.…”
Section: Discussionmentioning
confidence: 99%
“…The PPAS is a validated tool, reliable, and easy to use in evaluating the apprehension of the participants to receive electrical stimulation therapy [ 25 ]. The exclusion criteria included were (1) any contraindication for the use of diathermy by the emission of radiofrequency (tumours, use of implanted electronic devices as pacemakers, thrombophlebitis or deep venous thrombosis, pregnancy, active process of tuberculosis, fever, infected wounds, osteomyelitis, and rheumatoid arthritis) [ 17 , 26 , 27 , 28 ]; (2) having received a corticoid or hyaluronic acid injections treatment; (3) having reduced cognition or communication abilities; (4) or being currently involved in a medical-legal dispute. The use of basic analgesic drugs was allowed in order to avoid introducing significant changes in their treatment, but it was recorded to control possible changes that could influence in the final results.…”
Section: Methodsmentioning
confidence: 99%
“…PPAS is an easy-to-use, reliable, useful and validated tool in order to assess subjects' apprehension of receiving electrical stimulation therapy [21]. Exclusion criteria included all cases where the use of MDR was contraindicated (fever, active process of tuberculosis, pregnancy, infected wounds, osteomyelitis, tumors, presence of implanted electronic devices such as pacemakers, rheumatoid arthritis, thrombophlebitis or deep venous thrombosis) [22][23][24][25], and/or cases having received at any time treatment with corticoid or hyaluronic acid injections, cognitive or communicative impairment or being involved in a medical-legal dispute at the time. To avoid possible significant changes in the study, patients were asked to maintain their usual physical activity and treatments throughout the study, but they were allowed to use paracetamol; however, drug intake data was recorded to monitor any possible influence on final measurements.…”
Section: Participantsmentioning
confidence: 99%